Analysis of electromagnetic compatibility in local complexes of radioequipment - V. I. Mordachev; E. V. Sinkevich; D. A. Tsyanenka; Y. Y. Arlou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The technique for step-by-step computer-based analysis and diagnostics of electromagnetic compatibility (EMC) of radioequipment of complex on-board and local ground systems is improved. At the first stage of the analysis and diagnostics of EMC, all potentially dangerous paths of interference propagation are identified with the use of the broadband analytical worst-case model developed within IEMCAP program; the model allows to calculate spurious couplings between antennas of radioequipment. At the second stage, improved worst-case models for the potentially-dangerous interference propagation paths identified before development, and EMC analysis is performed iteratively on the basis of the refined models. The final stage is the discrete nonlinear EMC analysis, which is made using the high order nonlinearity models and radioreceivers' selectivity models obtained on the basis of the results of double-frequency testing of radioreceivers. The use of the developed technique makes it possible to achieve high efficiency of EMC analysis; this is proved by performing diagnostics of EMC for real-world on-board and local ground systems containing a set of HF, VHF, UHF and SHF radio equipment.